Relative Explosive Strength and Detonation Characteristics of Some Explosive Mixtures Containing Urea and Peroxides - Ahmed K. HUSSEIN (Wojskowa Akademia Techniczna, 2017)
Several mixtures, based on urea, urea hydrogen peroxide complex (UHP), triacetone triperoxide (TATP) with some inorganic oxidants were studied by means of ballistics mortar with TNT as a reference standard. The detonation pressure, P, detonation velocity, D, detonation heat, Q, and volume of gaseous product at standard temperature and pressure conditions (STP condition) were calculated by the mean of Explo5 V6.3. The relatively high explosive strength of some samples relative to the TNT charge, focuses on the positive influence of hydrogen peroxide presence in these mixtures, with advantage in the form of its complex with urea (i.e. as UHP). This influence connects with hydroxi-radical in the mixture under its initiation (as the first intermediate of this initiation reaction).
Keywords: Właściwości detonacyjne materiałów wybuchowych